(untitled) (Journal of Medicine, 2014)
A 19 yrs old male was admitted with upper abdominal pain and vomiting following ingestion of a fluid he thought to be beer. After repeated inquiry it was found that the clear fluid was Fog Juice, used to produce artificial Fog or Smoke on the stage. After 36 hours of ingestion the patient developed severe respiratory distress & itching. Investigation reports confirmed Acute Renal Failure & Hyperkalaemia. He was sent to Nephrology Unit for dialysis, but the poor victim expired there about 48 hours after ingestion. DOI: http://dx.doi.org/10.3329/jom.v14i2.19687 J Medicine 2013, 14(2): 195-197